Adesão de protozoários ̀a superfície de dispositivos intra-uterinos - Alvarenga, Vera Lucy de Santi [UNESP]; Pizzolitto, Elisabeth Loshchagin [UNESP]; Cicarelli, Regina Maria Barretto [UNESP] (My University, 2002)
Intrauterine devices (IUD) have been used by approximately hundred million of women in the world. IUD are unprescribed to women who have pelvic inflammation disease predisposition which is caused in general by non-treated sexually transmitted diseases (STD). Trichomoniasis, one of the most important vaginal infections, is caused by a flagellated protozoan, Trichomonas vaginalis, transmitted by sexual contact and also asyntomatic women are able to transmit it. The objective of this work was verify by scanning microscopy the adhesion of this protozoan on plastic and metalic IUD surfaces. IUD fragments were added in Diamond medium containing T. vaginalis and after 3 days at 37°C incubation, they were taken out and treated as necessary for scanning microscopy. The analysis showed showed the adhesion of the protozoans on plastic and metalic IUD surfaces. Even though the IUD were not yet directly associated with high incidence of the inflammation pelvic disease, it would become an infection reservoir of potencial pathogenic organisms.
Protozoan adhesion on intra uterine device (IUD) surface
Keywords: Adhesion; IVD; Trichomonas vaginalis; culture medium; diamond medium; disease predisposition; female; flagellum; human; incidence; incubation time; intrauterine contraceptive device; pathogenesis; pelvic inflammatory disease; prescription; protozoal infection; scanning electron microscopy; sexual transmission; sexually transmitted disease; surface property; trichomoniasis; vaginitis